Chatbot as a multi-age teaching strategy - Renó , Débora Liliane de Souza; Espina , Cátia dos Santos; Santos, Ricardo Rodrigues dos; Ferreira, William Nunes; Oliveira, Lucas Santos Medina de; Morales, Olivia Ines Alves (Seven Editora, 2023)
The awareness of contemporary students for the learning process comes up against the abundant and accelerated supply of technological resources. This scenario forces teaching to be attractive, dynamic and interactive throughout the construction of autonomous and meaningful knowledge. In this way, this work aims through the active methodology "Project Based Learning" to connect through the teaching of educational robotics students of different levels of education and provide them, through the making and execution of chatbot, a new tool for autonomous study, interactive and integrated to socio-emotional factors. StudyChat SESI-SP 113 was developed by 3rd year high school students using the Scrum method and offered to 5th year elementary school students as a new multidisciplinary study resource. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-058